2014
DOI: 10.1007/s00127-014-0948-3
|View full text |Cite
|
Sign up to set email alerts
|

The utility of estimating population-level trajectories of terminal wellbeing decline within a growth mixture modelling framework

Abstract: Whilst confirming other population-level analyses which support terminal decline and drop hypotheses in both mental health and wellbeing, we subsequently identified that most of this effect is driven by a small, but significant minority of the population. Instead, most individuals report stable levels of mental health and wellbeing in the years preceding death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…Future research should examine whether cognitive reserve serves as a protective factor even in a vulnerable population and life phase. Furthermore, previous research has shown that trajectories of terminal change for mental health and well-being are characterized by stability for most individuals [18]. It is an important question for future research whether nursing home residents can maintain mental health and well-being at the end of life despite cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should examine whether cognitive reserve serves as a protective factor even in a vulnerable population and life phase. Furthermore, previous research has shown that trajectories of terminal change for mental health and well-being are characterized by stability for most individuals [18]. It is an important question for future research whether nursing home residents can maintain mental health and well-being at the end of life despite cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used data from the last 3 years of life of 30,054 nursing home residents (69% women, age at death mean = 87.49 years, SD = 7.00 years, range = 65-103 years). In recent years, a growing number of studies have examined questions related to the heterogeneity of late-life development with latent class growth analyses [18][19][20][21]. In latent class growth analyses, the goal is to identify unobserved groups of individuals based on their longitudinal trajectories [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, the average decedent from the German SOEP study exhibited almost a full standard deviation (effect size units) decline in life satisfaction during the last four years of life. However, despite this overall negative picture of terminal decline in well-being, considerable individual differences exist (Burns, Byles, Magliano, Mitchell, & Anstey, 2014; Gerstorf & Ram, 2013). Although many people are exhibiting dramatic declines in well-being in the last years of their lives, there are some individuals who are able to maintain their well-being until (or very close to) the end of life.…”
Section: Well-being Trajectories In Adulthood and Late Lifementioning
confidence: 99%
“…In contrast, increasing evidence suggests that longevity does not necessarily correspond to inevitable disability and dependency among the oldest old, possibly owing to higher mortality among those with disability and illness in earlier older adulthood . Alternative perspectives emphasize capacity for psychological growth and maintenance of positive functioning and independence regardless of disease state, even in the years preceding death . It may be that as survivors relative to their birth cohort, older adults who reach very late life may report positive health and functional capacity despite increasing incidence of medical conditions .…”
mentioning
confidence: 99%
“…10 Alternative perspectives emphasize capacity for psychological growth 11 and maintenance of positive functioning and independence regardless of disease state, [7][8][9]12,13 even in the years preceding death. 14,15 It may be that as survivors relative to their birth cohort, older adults who reach very late life may report positive health and functional capacity despite increasing incidence of medical conditions. 7 The oldest old are therefore increasingly viewed as a unique population for whom more needs to be known regarding their capabilities and health status.…”
mentioning
confidence: 99%